(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Biodiversity of the Lugansk Nature Reserve: flora. / Compiled by: Sova T.V., Rusina N.V., Guz G.V., Borovik L.P., Shiyan-Glotova A.V. – Lugansk: Elton-2, 2009. – 130 p.